Rise and Fall of Ordinary Course Covenants and MAE Clauses: Case and Trend Analysis - Kwon, Matthew Hyung Kyun (Journal of Law and Commerce, 2023)
In the United States, the ordinary course of business provision has received inadequate attention in the field of corporate mergers and acquisitions. As anyone in the field is probably aware, the ordinary course of business covenant (“OC Covenant”) is one of the most common provisions included in almost every merger agreement. Illustrated by the fact that there are remarkably few notable precedents for the OC Covenant, despite its prevalence in merger agreements, notions of implementations and implications of the covenant have not drawn much attention from related professionals and scholars. In turn, material adverse effect provisions (“MAE Provision”) have been “The Beatles” of mergers and acquisitions in the United States. Since its increased practical relevance from the subprime mortgage crisis, many notable precedents have since proved and confirmed that the MAE Provision’s sophisticated and complex enforcement standards made this provision extremely difficult to execute in the real world. However, in actual merger negotiations the provision has never stepped down from its celebrity status. Many influential theorists view the MAE Provision as having absolute authority in connection with risk allocation during the time from signing agreements to closing the transaction, and with such recognition in past decades, the MAE Provision holds an untouchable significance by being perceived as an attractive route to call off agreed transactions in a crisis. This article proclaims that given recent trends in contract drafting and court decisions in connection with risk allocation during the interim period between signing and closing the merger, the role of the OC Covenant has been strengthened. To support this analysis, this article will proceed as follows. In Part I, this article will introduce the general features and background for the MAE Provision and the OC Covenant. In Part II, this article will introduce relevant risk allocation theories that have been suggested to govern risk allocation in order to present the history of important theories and their developments. In Parts III and IV, this article will examine features and developments of the MAE Provision and the OC Covenant with case examinations and literature analysis. The sections will refer to the 2021 data examination that Professor Guhan Subramanian conducted by examining 1,293 merger agreements in the MergerMetrics Database. The analysis will cover current structural shapes, as well as legal interpretation standards from meaningful precedents. Finally, in Part V, this article will propose a new understanding scheme for the risk allocation structure that implements and combines the academic theories, and drafting and litigation trends.